Morbidity of anterior iliac crest and calvarial bone donor graft sites: a 1-year randomized controlled trial. Issue 11 (November 2018) - Putters, T.F.; Wortmann, D.E.; Schortinghuis, J.; van Minnen, B.; Boven, G.C.; Vissink, A.; Raghoebar, G.M.
Abstract: Autogenous bone graft harvesting is still commonly considered the gold standard for the reconstruction of a severely resorbed maxillary alveolar ridge; however, the preferred donor site remains a subject of debate. This study compared the morbidity of calvarial and iliac crest donor sites after harvesting. Twenty edentulous patients with an insufficient volume of maxillary bone for reliable implant placement were assigned randomly to either calvarial ( n  = 10) or anterior iliac crest ( n  = 10) bone harvesting groups. All patients underwent a maxillary sinus floor elevation procedure combined with widening of the alveolar process using buccal bone blocks. Donor site morbidity was assessed before, during, and at 1 year after the surgery through patient questionnaires, physical examination, and medical records. No perioperative complications occurred. The anterior iliac crest group reported minor postoperative pain after harvesting. The scars after calvaria harvesting were significantly longer ( P  = 0.003), but this was not bothersome for the group of patients. Long-term pain was negligible and satisfaction was high in both groups. Both the calvaria and anterior iliac crest are associated with low long-term donor site morbidity and high patient satisfaction. Thus, patient-centred decision-making is appropriate when selecting the preferred harvesting method for that patient.